Role of mast cells in inflammation: Review of studies on human and experimental animal models [Mast hücreleri̇ni̇n enflamasyondaki̇ rolü: İnsan ve deneysel hayvan modelleri̇ üzeri̇nde yapilan çalişmalarin deǧerlendi̇ri̇lmesi̇] - (:unkn) unknown (My University, 2008)
Mast cells derived from bone marrow have a pivotal role not only in allergic and immunologic reactions but also in inflammatory reactions. Hence, the mast cells besides the activation of IgE, are activated with neurotransmitters and cytokins. As a result of these reactions, the mast cells are activated and release the present granule contents or newly (de novo) synthesized mediators to extracellular environment, participating in the inflammatory reactions. Hence, in the pathogenesis of diseases such as interstitial cystitis, inflammatory bowel disease and atopic dermatitis where an allergic basis is not assumed, it was shown that mast cells are activated and play a role in the inflammation process. In this review, the leading role of mast cells in the urinary bladder, skin, and gastrointestinal system, is discussed and evaluated in human and animal models.
Keywords: Experimental; Inflammation; Mast cell